Effects of Source Faulting and Fringing Reefs on the 2009 South Pacific Tsunami Inundation in Southeast Upolu, Samoa. Issue 12 (8th December 2020) - Bosserelle, Cyprien; Williams, Shaun; Cheung, Kwok Fai; Lay, Thorne; Yamazaki, Yoshiki; Simi, Titimanu; Roeber, Volker; Lane, Emily; Paulik, Ryan; Simanu, Lameko
Abstract: The subduction zone along the northern Tonga Trench has the highest plate convergence rate in the world, but limited records of its seismic and tsunamigenic activities. In 2009, a tsunami generated by an M W 8.1 earthquake doublet caused severe impacts in the region including damage and loss of life on the south shores of Upolu and Savaii Islands, Samoa. Here, we use numerical modeling aided by recorded data and eyewitness accounts to evaluate and identify the published source models in the Tonga Trench region that most suitably represent the 2009 event for use in hazard assessment around Samoa. We show that only a few of the published sources are suitable to reproduce the large inundation observed in Samoa, and none reproduces runup as high as observed in the areas that were most severely impacted on the southeast Upolu coast. The distribution and intensity of runup and inundation are dependent on source model, local topographic and bathymetric features, regional coastal geomorphology, and trapping of short‐period waves over the reef flats. The computed results are also influenced by model approximation and grid resolution especially for areas with extreme runup records. Comparison of the relative contributions from the doublet to the southeast Upolu inundation indicates that the initial intraplate normal faulting dominated the east‐northeastward tsunami propagation and inundation compared with the subsequent interplate thrust faulting. Overall, two key source models are discussed and identified for future refinement. Plain Language Summary: This study models the September 29, 2009 tsunami in Samoa and compares model outputs with tsunami water level observations, field data of runup and inundation as well as eye‐witness accounts collected after the event occurred. Whilst several studies have reconstructed the runup and inundation of this event in American Samoa, this is the first time such work has been undertaken in Samoa which lies to the west (formerly known as Western Samoa). We discuss the effects of the complex earthquake sequence that triggered the tsunami event, as well as influence of nearshore coastal characteristics on the pattern and behavior of tsunami impacts observed onshore. Key Points: The tsunami water level produced by the 2009 earthquake doublet is simulated for Samoa and compared to observed runup on southeast Upolu Geometry of the intraplate normal faulting near the northern Tonga Trench terminus influences the extreme runup on southeast Upolu The runup on southeast Upolu is also dependent on fine‐scale topographic features and wave excitation over the reef flats